Conjugate addition of a silyl ketene acetal to alpha,beta-unsaturated lactones - Gnaneshwar, Rudhramyna; Sivaram, S (Synthetic Communications, 2006)
{Conjugate addition of a silyl ketene acetal [
Keywords: acetals; deprotection; MoO3/SiO2; protection

Novel method for the protection of amino alcohols and carbonyl compounds over a heterogeneous, reusable catalyst - Srivastava, P.; Srivastava, R. (Catalysis Communications, 2008)
A novel application of Al-SBA-15 catalyst in the protection of amino alcohols and carbonyl compounds is reported. N-t-butoxy carbonyl [N(Boc)] amino alcohols were protected using 2,2-dimethoxyproparic (DMP) to form acetonides. Acetonide deprotection was also studied using the same catalyst to obtain the parent amino alcohol. Protection of carbonyl compounds was Studied using neopentyl glycol, ethylene glycol and propylene glycol as the protecting agents. A series of commercially important molecules Such as 2-substituted and 2,2-disubstituted 1,3-benzodioxoles were synthesized by reacting carbonyl compounds with catechol. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Acetalization; acetonide; Amino alcohol; benzodioxole; protection